Metaphysical essays - Hawthorne, John (John P.) (Oxford : Clarendon, 2006)
Hawthorne offers original treatments of fundamental topics in philosophy, including identity, ontology, vagueness, and causation. Six of the essays appear here for the first time, and there is a valuable introduction to guide the reader through the selection.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Metaphysics